Impact Assessment of the Causes and Prevention of Farm Accidents on Mechanized Farms of North Central Zone/States of Nigeria - Yohanna, J. K; Fulani, U. A; Ode , S; Ali , H. K (Asian Journal of Agriculture and Rural Development, 2012)
Accidents occurring on mechanized farms have been a thing of concern to farmers and researchers both within and outside Nigeria. An investigation into the causes and prevention of farm accidents on mechanized farm was carried out in Benue, Federal Capital Territory, Kwara, Nasarawa, Niger and Plateau states that constitute the north central zone/states of Nigeria. The data collection instrument was a questionnaire designed and distributed to all the states mentioned. The questionnaire addressed demographic variables and issues linked directly with the types, causes and prevention of farm accidents. A total of 2283 tractors were available in the mechanized farms surveyed, while a total of 1014 constituted other farm machinery/equipment. Results show that 81.7% of accidents victims are male. About 45.5% of the accident victims were aged between 40years and above. About 33.96% of the minor accidents resulted in slight damage to equipment and machinery. Similarly 43.4% of accidents resulted in substantial loss in time, while about 22.64% of accidents resulted in medical attention. There was no attempt made to quantify the monetary terms of the cost of each accidents, as there was dearth of information. The results obtained in this work are in agreement with the previous studies both outside and inside Nigeria. Also, from this survey work, there was a problem of good record keeping in most of the establishment surveyed. It is therefore, recommended among other things that adequate training and retraining of tractors/machinery operators should be carried out periodically, to intimate operators on recent use of farm equipment due to environmental and human factors